Análisis jurídico del potencial de comercialización de los servicios ambientales en el Ecuador - Vallejo Ochoa, Natalia Salomé (2024)
The legal analysis of the commercialization potential of environmental services in Ecuador is a highly relevant topic today. In the context of Ecuador, the sustainable management of natural ecosystems has faced challenges in reconciling environmental conservation with economic growth. For a long time, conservation and economic development seemed incompatible, but recent advances have shown that sustainably managed forests generate high economic values, income for the sector, support for communities, and essential services for human survival. The objective was to analyze Ecuadorian environmental regulations to formulate proposals that enable the sustainable commercialization of environmental services in Ecuador. This research employs a mixed approach, integrating both quantitative and qualitative elements in its design and execution. The methodology used for the surveys was based on a stratified sampling approach. The findings of the research reveal a high familiarity with the concept of environmental services, with a significant focus on services such as water catchment and filtration, waste treatment, and biodiversity protection, among others. There is a widespread perception that current legislation in Ecuador does not support the commercialization of these services (77.8%), which has generated strong consensus (94.9%) in favor of amending the constitution to promote the sustainable commercialization of environmental services. The constitutional reform should reflect a balance between environmental protection, defining who will be responsible for their management, establishing mechanisms for economic valuation, and recognizing the rights of local communities, ensuring that environmental services are valued, conserved, and used sustainably for the benefit of present and future generations in Ecuador